Landscape ecological risk assessment and influencing factor analysis of basins in suburban areas of large cities – A case study of the Fuchunjiang River Basin, China - Cheng, Xiaomeng; Zhang, Yaping; Yang, Guofu; Nie, Wenbin; Wang, Yinyi; Wang, Jing; Xu, Bin (Frontiers in Ecology and Evolution, 2023)
Abstract: Landscape ecological risk reflects the impact of human activities or natural hazards on landscape patterns, functions, and processes in a region. The scientific assessment of its evolutionary trends can play an essential role in maintaining and improving regional human well‒being. This study focused on the Fuchunjiang River Basin in the suburbs of Hangzhou, a large city in China with a high degree of landscape heterogeneity and rapid economic growth. Based on land use data from 1990 to 2020, an ecological risk assessment model and geodetector tools were combined to study the spatiotemporal variation characteristics and influencing factors of landscape ecological risk in the basin. The results showed the following: (1) from 1990 to 2020, the landscape pattern of various land use types showed a general trend of an increasing degree of agglomeration and decreasing loss index; (2) The spatial distribution pattern of landscape ecological risk was "high in the northwest and low in the southeast". From basin to township scales, landscape ecological risk showed a decreasing trend on long time scales, although the changes were relatively drastic in short time periods; (3) GDP, human interference, area of urban and rural residential land, area of arable land transferred in, and area of arable land transferred out were the dominant influencing factors of landscape ecological risk; (4) the coupling between landscape ecological risk and GDP in 2020 exhibited an inverted "U" shaped relationship, indicating that the environmental Kuznets curve (EKC) may have the same applicability in the ecological risk management; (5) according to the main functions of different risk agglomerations, targeted ecological risk management strategies were proposed. In short, this study carried out the landscape ecological risk assessment at the township scale for the first time, quantitatively analyzed the relationship between economic development and ecological risk, and proposed targeted risk prevention strategies, which are instructive for other basin areas that are experiencing rapid urbanization in the world.